Novel soft-switching DC-DC converter with full ZVS-range and reduced filter requirement. II. Constant-input, variable-output applications. - Ayyanar, R. (IEEE Transactions on power electronics)
For pt.I see ibid., vol.16, no.2, p.184-92 (2001). The performance of the hybrid converter featuring zero-voltage-switching (ZVS) down to no-load and significant reduction in the filter requirement, proposed in Part I of this paper, is analyzed here for constant-input, variable-output applications. For these applications, the main drawback of the hybrid converter, namely the increased transformer rating is eliminated. The advantages of the hybrid configuration like the reduction in filter rating and full-load ZVS with negligible penalty on conduction loss, are retained. An extension of the basic hybrid converter-a combination of two full-bridges using six switches is proposed. This configuration is well suited for applications above a few kilowatts, and results in significant reduction in the ripple current rating of the input filter capacitor. Experimental results obtained from a 1 kW/100 kHz prototype are presented